Passive Synchronization Based Energy-Efficient MAC Protocol over M2M Wireless Networks. (20th November 2013) - Sthapit, Pranesh; Pyun, Jae-Young
Providing diverse quality-of-service (QoS) with ultra-low power consumption and mobility support is the most important and challenging issue in machine-to-machine (M2M) networks. In a typical beacon-enabled network, nodes need to wake up for receiving periodic beacon in order to maintain synchronization. Here, we present a new MAC protocol called passive-synchronization-based energy-efficient MAC (PSMAC) that synchronizes nodes in their sleep state by using interrupt generated from the proposed radio-triggered hardware. In order to activate the radio-triggered hardware, the synchronization frame is broadcast, but in a separate channel called synchronization channel, so that interrupts are not generated during data transmission. This synchronization frame is also used for providing the fast and energy-efficient association. Network information is embedded into the synchronization frame so that mobile nodes can learn about their neighbors just by scanning the synchronization channel. Furthermore, by positioning the beacon period after the contention access period, PSMAC provides fast and preemptive slot allocation that can handle diverse QoS requirements. We compare PSMAC with IEEE 802.15.4 and show that PSMAC has much better performance in node association time, energy efficiency, and faster data delivery at the cost of additional radio-triggered hardware and a dedicated channel.